Pendidikan Seksual (Kesehatan Reproduksi & Personal Hygiene pada Masa Menstruasi) dan Pengukuran IMT pada Remaja - Andini, Tressia; Brett Nito, Paul Joae; Destriani, Rizka Mariyana; Juniawinata, Resa; Chaidir, Shaila; Widia, Widia; Yelika, Yelika; Dano, Rebecca Nathalie; Dhea Manto, Onieqie Ayu (JURNAL SUAKA INSAN MENGABDI (JSIM), 2024)
World Health Organization (WHO) in 2019 has surveyed several countries and found that many adolescent girls aged 10-14 years experience reproductive health problems, among the problems experienced are reproductive tract infections. 2012 statistical data in Indonesia shows that the menstrual hygiene behavior of adolescents at the age level of 10-14 years is still in the poor category. Therefore, it is necessary to conduct sexual education to raise awareness of adolescent girls about the importance of menstrual hygiene and nutritional status. The purpose of the health education carried out is to increase the knowledge of adolescent girls related to maintaining nutritional intake, reproductive health, especially during menstruation. The method used in this health education is the lecture and question and answer method, carried out for 2 weeks of work. The first week was the distribution of Pre Test, TB measurement and weight weighing. In the second week, the material was presented using ppt media, leaflets and posters, followed by oral evaluation and completion of the Post Test. Increased knowledge of adolescent girls after health education on proper personal hygiene, and good self-care during menstruation.